Polbeng Research Vessel Comfort Study in the Malacca Strait - jamal jamal; Muhammad Alimul Hafiz; Budhi Santoso; Berlian Arswendo Adietya; Suardi; Juanda (Indonesian Journal of Maritime Technology, 2026)
The Polbeng Research Vessel is a small research ship developed by Politeknik Negeri Bengkalis (Polbeng) in collaboration with CV. Fatih Bahari Engineering. The vessel is constructed from High Density Polyethylene (HDPE) and has principal dimensions of 9 m length overall (LOA), 2.2 m breadth, and 1.2 m depth, powered by an 85 HP outboard engine. This study aims to evaluate the seakeeping and motion comfort performance of the vessel to support research activities involving personnel and onboard equipment. The seakeeping analysis is conducted using a frequency-domain approach based on Response Amplitude Operators (RAOs), where ship motions are evaluated under regular wave conditions. Four operational cases are considered, involving two wave heights (0.2 m and 0.4 m) and two wave encounter directions, namely beam seas (90°) and head seas (180°). Three ship motions are analyzed: heave, roll, and pitch. The results indicate that roll motion in beam seas conditions exhibits the most significant response compared to other motions, which is consistent with the theoretical characteristics of small vessels having shorter restoring arms for roll motion. Overall, the vessel’s motion responses remain within acceptable limits and satisfy established comfort criteria based on NORDFORSK 1987, STANAG 4154, U.S. Coast Guard (USCG), ISO 2631/1, ISO 2631/3, and BS 6841:1987 standards. The findings provide technical insight into the seakeeping behavior and comfort performance of HDPE-based small research vessels and serve as a reference for the design, evaluation, and development of environmentally friendly research and working vessels to enhance operational safety and effectiveness.